Status Epilepticus in Children: Experience in a Portuguese Tertiary Hospital - Catarina Granjo Morais; Marta João Silva; Teresa Cunha Mota; Ruben Rocha; Augusto Ribeiro (Korean Child Neurology Society, 2023)
Purpose Status epilepticus (SE) is a life-threatening neurological emergency, frequently diagnosed in pediatric patients. We aimed to characterize our pediatric cases of SE in an 11-year period according to the 2015 International League Against Epilepsy report. Methods Clinical electronic records were retrospectively reviewed. All pediatric SE cases admitted from January 2010 to December 2020 were included, excluding neonates. SE was considered refractory if it persisted despite the administration of two appropriate antiseizure medications at acceptable doses. Results We included 102 episodes, 55 (53.9%) in boys. The median age was 2.5 years (interquartile range, 1.3 to 5.0). Most episodes were classified as SE with prominent motor features (92.2%), and the most frequent etiological classification was acute symptomatic cause (84.3%). A benzodiazepine was used as the first-line antiseizure medication in 99 (97%) cases, of which diazepam was preferred (93%). The preferred second-line medication was phenytoin (65.7%). Midazolam was the most frequently responsible for termination of SE when given in a continuous infusion (47%). Episodes of SE were classified as refractory in 81 (79.4%) cases. Episodes of >60 minutes were more frequent in patients diagnosed with epilepsy (P=0.036), focal motor SE (P<0.001), and non-convulsive SE (P=0.037). The in-hospital mortality rate was 2.9%. Conclusion Most of our findings are in accord with the current literature. Epilepsy, non-convulsive SE, and focal motor SE were associated with prolonged duration (>60 minutes), which reinforces the significance of the underlying neurological disease and semiological standardization in pediatric SE.